Comparison of high‐power and conventional‐power radiofrequency energy deliveries in pulmonary vein isolation using unipolar signal modification as a local endpoint. (15th May 2020) - Ejima, Koichiro; Higuchi, Satoshi; Yazaki, Kyoichiro; Kataoka, Shohei; Yagishita, Daigo; Kanai, Miwa; Shoda, Morio; Hagiwara, Nobuhisa
Abstract: Introduction: Negative component abolition of the unipolar signal (unipolar signal modification [USM]) reflects the lesion transmurality. The purpose of this study was to compare the procedural safety and outcome between high‐power and conventional‐power atrial radiofrequency applications during a pulmonary vein isolation (PVI) using USM as a local endpoint. Methods and Results: High‐power (50 W) and conventional‐power (25‐40 W) applications were compared among 120 consecutive patients with paroxysmal atrial fibrillation who underwent a USM‐guided PVI. The first 60 patients were treated with conventional‐power (CP) group and last 60 with high‐power (HP) group. The atrial radiofrequency applications lasted for 5 to 10 seconds (CP group) or 3 to 5 seconds (HP group) after the USM. All procedures were performed using 3D mapping systems with image integration and esophageal temperature monitoring. The baseline characteristics were similar between the two groups. The HP group had fewer acute PV reconnections (62% vs 78%; P = .046) and a reduced procedure time (119.3 ± 28.1 vs 140.1 ± 51.2 minutes; P = .04). Freedom from recurrence after a single ablation procedure without any antiarrhythmic drugs was higher in the HP group than CP group (88.3% vs 73.3% at 12‐months after the procedure, log‐rank; P = .0423). There were no major complications that required any intervention. Conclusions: The high‐power PVI guided by USM decreased the procedural time and may improve the procedural outcomes without compromising the safety.